Anatomy of picture archiving and communications systems: nuts and bolts -- image acquisition: getting digital images from imaging modalities...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Andriole KP (Journal of Digital Imaging)
Digital acquisition of data from the various imaging modalities for input to a picture archiving and communication system (PACS) is discussed. Essential features for successful clinical implementation including Digital Imaging and Communications in Medicine (DICOM) compliance, radiology information system (RIS)/hospital information system (HIS) interfacing, and workflow integration are detailed. Image acquisition from the inherently digital cross-sectional modalities are described, as well as digital acquisition of the conventional projection x-ray using computed radiography (CR), direct digital radiography (DDR), and film digitizers. Copyright (c) 1999 by W.B. Saunders Company